EFEKTIVITAS PUPUK ORGANIK CAIR LIMBAH TAHU DALAM MENGURANGI PUPUK NPK PADA TANAMAN MENTIMUN - Rosmiah Rosmiah; Neni Marlina; Iin Siti Aminah; Heru Agung Sandika; Fitri Yetty Zairani; Burlian Hasani; Laili Nisfuriah (Jurnal Penelitian Pertanian Terapan, 2022)
The Effectiveness of Tofu Liquid Waste Organic Fertilizer in Reducing NPK Fertilizer in Cucumber Plants. Tofu waste contains macro nutrients (NPK) and micro nutrients (Fe, Cl, Mn, Cu, Zn). Tofu waste has the potential to become liquid organic fertilizer (POC). The advantages of tofu waste can reduce the use of NPK on cucumber plants. The purpose of this study was to determine the effectiveness of tofu liquid wate oerganic fertilizer in reducing NPK fertilizer in cucumber plants. This research was conducted in farmers' fields on Jalan Sukarela, Kebun Bunga Kelurahan, Sukarami District Km 7 Palembang, South Sumatra, from July to October 2020. Separate plot design was used with 9 treatment combinations that were repeated 3 times. Main plot of tofu waste POC: without (P0), 180 ml / l (P1), and 360 ml / l (P2). Plot Children Percentage of NPK fertilizer from recommended dose (N): 25% (N1), 50% (N2) and 75% (N3). The results showed that the tofu waste POC 360 ml / l of water was very effective in reducing the use of NPK fertilizer by 50% of the recommended dose and increasing the cucumber yield by 472,17% when compared without giving tofu waste POC and NPK fertilizer 25 %